COLLECTION OF THE EDIACARIAN (VENDIAN) FOSSILIZED FAUNA FROM THE DNISTERSIDE IN THE GEOLOGICAL MUSEUM OF THE KYIV NATIONAL TARAS SHEVCHENKO UNIVERSITY AS A NATIONAL PROPERTY OF UKRAINE - NESTEROVSKYI, V.; FURDUI, R.; VAKULENKO, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
It is proposed to announce the collection of the ediacarian (vendian) fossilized fauna from Dniesterside keeping in the geological museum of the Kyiv national Taras Shevchenco University as a national property of Ukraine.